Posttraumatic Stress Disorder and Related Disorders among Female Yazidi Refugees following Islamic State of Iraq and Syria Attacks—A Case Series and Mini-Review - Gerdau, Inga; Kizilhan, Jan Ilhan; Noll-Hussong, Michael (Frontiers in Psychiatry, 2017)
Following the severe attacks by the so-called ´Islamic State of Iraq and Syria’ (ISIS) on the Yazidi population, which started in summer 2014, the state government of Baden-Württemberg, Germany, funded a Special-Quota Project to bring 1000 very ill or left-behind women and children who were being held hostage to 22 cities and towns in Baden-Württemberg to receive integrated care. Here we report for the first time on the cases of 4 Yazidi women living in Ulm, Germany, focusing on the clinically observed and psychometrically assessed mental phenomena or disorders. Our primary aim was to explore what ICD-10 diagnoses are present in this population. Although highly traumatized, these women were suffering primarily from adjustment disorder rather than post-traumatic stress disorder (PTSD) according to official classification systems. Despite their symptoms of depression and anxiety the women’s responses to self-assessment questionnaires provided no evidence of compulsion, somatization or eating disorders. The results suggest that further investigation of the individual-level effects of rape and torture, as well the historic, systemic and collective effects, e.g., on families and societies, is required.